Profile of Interactive Learning Media Based Digital Literacy Needs on Elemental Chemistry Concepts - Hayuni Retno Widarti; Diah Triwidiastuti; Deni Ainur Rokhim (Jurnal Tadris Kimiya, 2022)
Interactive learning media integrated with technology are needed to facilitate the explanation of abstract material, including elemental chemistry. The study aims to analyze the profile of interactive learning media-based digital literacy needs on elemental chemistry concepts in high school students. The research uses a descriptive qualitative research method. The subjects of this study consisted of chemistry teachers and high school students from four sub-districts in Trenggalek Regency. Based on perspective of teachers and students, they need learning media that can help explain abstract material to be more communicative and interactive to increase learning effectiveness. The results of questionnaire answers show the application of interactive digital learning media based digital literacy from the teachers and students are 39% and 37%, respectively. The percentage shows that digital literacy-based learning media is still lacking. Furthermore, interactive learning media based on digital literacy could be developed to fulfill a need using specific criteria.